ENCRYPTION APOCALYPSE? PREPARING DATA SECURITY FOR THE QUANTUM COMPUTING ERA - Kiran Iqbal; Zainab Ali; Bilal Aslam (Yayasan Adra Karima Hubbi, 2025)
The imminent maturation of quantum computing threatens to nullify the mathematical hardness underpinning global Public Key Infrastructure, creating an urgent “Harvest Now, Decrypt Later” vulnerability. This study investigates the operational feasibility of transitioning to NIST-standardized Post-Quantum Cryptography (PQC) protocols within heterogeneous network environments. Utilizing a rigorous quantitative benchmarking framework, we evaluated the performance of lattice-based primitives, specifically ML-KEM and ML-DSA, against classical standards across high-performance servers and resource-constrained IoT devices. Empirical data reveals a fundamental architectural paradigm shift: while PQC algorithms exhibit superior computational execution speeds, they introduce severe transmission overheads, resulting in memory saturation and packet fragmentation on edge hardware. Results demonstrate that hybrid encryption schemes provide valid risk mitigation but incur statistically significant latency penalties due to expanded artifact sizes. We definitively conclude that the “Encryption Apocalypse” is primarily a bandwidth and memory bottleneck rather than a computational one, mandating the immediate deployment of adaptive crypto-agility frameworks to manage the infrastructural constraints of the post-quantum era.